Slovar slovenskega knjižnega jezika – dinamika pomenskih sestavin - Vidovič-Muha, Ada (Slavistična revija, 2022)
The central theme of the discussion is primarily related to semantic features as those content properties of the lexeme that define the meaning. As such, they play a fundamental role both in the emergence of polysemy of an individual lexeme and in establishing the expressive and semantic relationship between lexemes. They are embedded in the syntagmatic and paradigmatic aspect of the language system.
Keywords: denotative meaning; denotativni pomen; Dictionary of the Slovenian standard language; endogeni leksem; endogenous lexeme; leksem; leksikalni pomen; lexeme; lexical meaning; pomenska sestavina; semantic feature; Slovar slovenskega knjižnega jezika; Slovene; slovenščina